PEMANFAATAN MAGGOT SEBAGAI PENGGANTI TEPUNG IKAN DALAM PAKAN BUATAN UNTUK BENIH IKAN BALASHARK (Balanthiocheilus melanopterus Bleeker) - Agus Priyadi; Zafril Imran Azwar; I Wayan Subamia; Saurin Hem (Jurnal Riset Akuakultur, 2009)
Penelitian bertujuan untuk mengetahui pengaruh substitusi sumber protein tepung ikan dengan tepung maggot telah diteliti terhadap ikan hias balashark. Sebanyak 1.500 ekor benih ikan balashark dengan bobot awal rata-rata 2,26 ± 0,08 g dan panjang 5,18 ± 0,06 cm ditebar dalam 15 unit bak tembok berukuran 1,2 m x 0,7 m x 0,5 m, sistem resirkulasi dan dilengkapi aerasi dengan padat penebaran 100 ekor/bak dan dipelihara selama 60 hari. Pakan buatan dengan perbedaan substitusi maggot terhadap tepung ikan sebagai pengganti protein diberikan sebagai perlakuan yaitu (a) 0%; (b) 10%; (c) 20%; (d) 30%; dan (e) 40% maggot substitusi. Perlakuan substitusi maggot nyata mempengaruhi (P<0,05) pertambahan bobot, panjang total, pertumbuhan spesifik, retensi protein, dan rasio efisiensi protein. Substitusi maggot hingga level 16,47% memberikan respons terbaik terhadap penampilan tumbuh benih ikan balashark.The objective of this research was to study the effect of maggot meal as an alternative protein source to partially substitute fish meal in artificial feed for balashark fry. This research was conducted at the Research Institute for Ornamental Fish in Depok, West Java. Fifteen concrete tanks each of 1.2 m x 0.7 m x 0.5 m, provided with aerated recirculation water system, were used as culture tanks. Balashark fry averaging 2.26±0.08 g in body weight and 5.18±0.06 cm in body length were stocked into the tanks at a density of 100 fries per tank. The dietary treatments tested were five different levels of maggot meal, namely: (a) 0% substitution; (b) 10% substitution; (c) 20% substitution; 30% substitution, and e) 40% substitution. Feeding of the fries lasted for 60 days. Results of the research showed that, based on body weight gain, total body length, specific growth rate, protein retention, protein efficiency ratio, and lipid retention, the effect of maggot meal to substitute for fish meal was significant (P<0.05). The best growth performance of the balashark fries was achieved by the feed containing maggot meal substitution for fish meal of 16.47%.